THE ENERGETIC PERFORMANCE OF OLD BUILDINGS: HOW TO IMPROVE IT? - Ramos, Ana Ferreira; da Silva, José Mendes (European Scientific Journal, ESJ, 2015)
Along the years, in Portugal, the built environment was left behind and the straights were devoted for new buildings, creating new urban areas sometimes unattached from the existing city. The construction before the 80’s is compromised by its thermal quality if we consider that the thermal codes and the worry about thermal buildings behavior only came up around 90’s. In this work, the buildings from old city centers and its characteristics were studied as well as some intervention actions accurate for this construction and its results in terms of thermal performance. For this study a simulation tool was used, namely the Design Builder, and the results of these simulations were presented in order to understand the improvement in its thermal behavior when compared with its original conditions. It is possible to improve considerably the interior comfort and buildings thermal behavior with respect by architectonic characteristics and keeping constructive solutions and material with interventions actions that are compatible with existing structures.